KOMPARASI KURIKULUM 2013 DAN KURIKULUM MERDEKA DALAM PENDIDIKAN NILAI, KARAKTER DAN AKHLAK - Zainal Arifin; Rizky Maulana Aziz; Mukh Nursikin (JMPT: Jurnal Manajemen Pendidikan Tihamah, 2023)
Changes in the existing curriculum in the world of Indonesian education have made the learning process change in line with developments over time. The Merdeka Curriculum and the 2013 Curriculum both aim to form a generation with integrity and a strong personality, so that the development of educational values, character and morals becomes essential in modern education. This is an important step in efforts to form individuals who are cultured, have noble character, and are able to face increasingly complex and dynamic changes in today's world. This research uses a qualitative methodology with a library research approach that utilizes theories related to research problems. Data was collected through literature studies, by reviewing books, articles, papers and relevant materials about the impact of education on personality formation. Primary data sources are written materials such as books, papers, and reference materials, while secondary sources are notes about library sources. Data analysis was carried out in three stages: data reduction, data presentation, and drawing conclusions, which became the basis for writing this scientific work. This data collection and analysis method is used to investigate the relationship between education and character formation. The 2013 Curriculum and the Merdeka Curriculum have different approaches regarding character education. The 2013 curriculum integrates character in school subjects and activities, while the Merdeka Curriculum emphasizes explicit character with a national focus. Even though they are different, both aim to form a strong generation. Unfortunately, the implementation of the Merdeka Curriculum without teacher consideration has confused especially older teachers, even though the formation of student character is basically similar: the 2013 Curriculum integrates character in subjects, while the Merdeka Curriculum gives schools flexibility in approaching character according to student needs.